Rethink Retraining: A Review - Susant Mohanty1, Kalimireddy L. Priyanka2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
As we advance with time, there is a change in the attitude of the kids and their parents which in turn demandsa change in the pediatric dentist’s approach to them. When we treat young children, there is an addedresponsibility to gain their co-operation for rendering the best treatment. Sometimes, the added challengewill be to gain the confidence and co-operation of the child as well as the parents with a previous unpleasantdental experience. Hence, there is a need to re-evaluate the retraining of a patient by considering advancedand innovative behavioral guidance and management techniques.